(untitled) (Biological Sciences - PJSIR, 1999)
Biodegradation of rice straw with Pleurotus spp. enhanced its nutritive value. The protein contents increased from 1.7 to 9.40% and crude fibre, cellulose and lignin decreased from 32.6 to 17.4%,35.0 to 18.2% and 10.9 to 8.5%, respectively. Reticula-rumen digestibility of dry matter, cellulose, minerals and protein contents of rice straw, biodegraded by different Pleurotus spp., was enhanced from 37.0 to 46.8%, 49.9 to 61.0%, 20.1 to 29.3% and 31.4 to 43.9%, respectively over the non-degraded rice straw.